Clinical Significance of Serum Haptoglobin and Protein Disulfide-Isomerase A3 in the Screening, Diagnosis, and Staging of Colorectal Cancer - Niu, Yajin; Xue, Jun; Wu, Xueliang; Qu, Ming; Wang, Likun; Liang, Weizheng; Li, Tian (Frontiers in Pharmacology, 2022)
Objective: This study aims to explore the clinical significance of haptoglobin (HP) and protein disulfide-isomerase A3 (PDIA3) in human serum in the screening, diagnosis and staging of colorectal cancer (CRC), and to provide novel screening approaches featuring high specificity, sensitivity, and accuracy for early screening and diagnosis of clinical colorectal cancer. Methods: 88, 77, and 36 blood specimens were respectively harvested from colorectal cancer patients, colorectal polyp patients, and healthy subjects who requested medical assistance from our hospital between October 2019 and February 2022. The serum contents of HP and PDIA3 in each sample were determined through an enzyme linked immunosorbent assay (ELISA). This step was taken to analyze the differences among different specimen groups in terms of the serum contents of HP and PDIA3, to analyze the relationships between the expression levels of HP and PDIA3 and the pathological characteristics of colorectal cancer, and to explore the critical role of HP and PDIA3 in the screening, diagnosis, and staging of colorectal cancer. Results: Serum contents of HP and PDIA3 were higher in colorectal cancer patients, with statistical differences (P < 0.05), than those in the colonic polyp patients and healthy subjects. ROC curve demonstrated that the cut-offs of HP and PDIA3 serum contents indicating colorectal cancer were 149 ug/ml and 66 ng/ml respectively. The individually and jointly tested AUCs of HP(0.802) and PDIA3(0.727) were higher than those of serum CEA and CA199, the sensitivity and specificity of HP were 64.8% and 91.2%, the sensitivity and specificity of PDIA3 were 65.9% and 71.7% . Moreover, the contents of HP and PDIA3 increased alongside disease progression, with differences (P < 0.05). Conclusion: Our research indicated that joint testing of the two (i.e., HP and PDIA3) was of reference value to disease the assessment of the progressive stage. Serum HP and PDIA3 can be deemed accurate and reliable biological indicators of colorectal cancer screening.